(untitled) (Revista de Artes Marciales Asiáticas, 2018)
This article provides an examination of archery techniques, such as drawing techniques of the bowstring, the method of grasping the bow grip and placing the arrow, and their relationship to warfare as depicted on 22 Sassanian and early post-Sassanian silver plates. These plates provide useful information on Sassanian archery equipment and techniques. These plates can be categorized into the following categories: (a) foot archery, (b) horse archery, c) dromedary archery and (d) elephant archery. All plates examined in this study depicting these categories are in a hunting milieu. The largest proportion of plates pertain to horse archery which in turn can be classified into four combat subsets: forward-facing horse archery, the backward-firing Parthian shot, horse archery with stirrups, and horse archery while appearing to ride backwards.